PENGARUH KONSENTRASI SUBLETHAL DIAZINON 60 EC TERHADAP PERKEMBANGAN AWAL EMBRIO BULU BABI ECHINOMETRA MATHAEI - Markus T. Lasut, dkk (EKOTON, 2012)
Diazinon is one of insecticides used to control pests and other organisms. However, diazinon may have negative impact to aquatic ecosystem since its application in agriculture is uncontrolled. The present experiment aims to determine the effect of diazinon (insecticide) in sublethal concentration on embryonic development of sea urchin Echinometra mathaei. The experiment was designed by using toxicity test technique in which a number of eggs and sperms of the sea urchin were exposed into seawater with 0.3, 0.6, and 3 ppm of diazinon concentrations and a control (0 ppm). Percentage of developing larvae were accounted and time of each embryonic development stage was recorded. The result shows the range of sublethal concentration of diazinon is 0.06 to 0.6 ppm. Mean percentage of developed larvae for concentration of 0.3, 0.6, 3 and the control are 29.23, 40.07, 62.11, and 82.28, respectively. Mean time for the first, second, third, fourth, morula, hatching and larvae development stages are 87.41, 158.08, 188.75, 227.83, 269.83, 523.75, and 2122.41 minutes, respectively. Even though diazinon in sublethal concentration was not affect the development time, it is for mortality of larvae.